SATUA I DEMPUAWANG ANALISIS STRUKTUR DAN FUNGSI - Dewi Ratih, I Gusti Ayu (Humanis; Volume 4. No. 3. September 2013, 2013)
This study discusses Satua I Dempuawang (SID) with the analysis of the structure and function. The purpose of this study, namely, to preserve and develop the cultural values Bali especially on traditional literature. While this study specifically aims to reveal the structure and narrative form in the SID and describes the functions contained therein. Methods and techniques used in this study were divided into three stages, namely the provision of methods and techniques of data consisting of methods refer to techniques of translation, sorting techniques, and engineering record, methods and techniques of data analysis consisted of descriptive qualitative method with analytic techniques, and presentation of the methods and techniques of data analysis consisted of informal methods; deductive-inductive techniques. The results obtained in this research, there is a structure in terms of the structure of narrative forms and structures. Structure which includes the form of the SID code language and literature, language diversity, and style. SID includes incident narrative structure, plot, character and characterization, setting, theme, and the mandate. Analytic functions in the SID that is exposing and explaining the functions contained in the SID story. Later in the analysis of the general functions of the SID functions contained in the SID associated with the events experienced by the characters or actors called function. Actors function has a very important role. Without the actors or characters in an unlikely story of the event can occur, so that the perpetrators greatly affect the storyline.
Keywords: structure form, narrative structure, and function